Simulating of Top-Cross system for enhancement of antioxidants in maize grain - Vancetovic, Jelena; Zilic, Sladjana; Bozinovic, Sofija; Ignjatovic-Micic, Dragana (Spanish Journal of Agricultural Research, 2014)
Blue maize (Zea mays L.) is grown for its high content of antioxidants. Conversion of yellow and white to blue maize is time consuming because several genes affect blue color. After each backcross selfing is needed for color to be expressed. In order to overcome the problem of time and effort needed for conversion to blue kernel color, we have set a pilot experiment simulating a Top-cross system for increasing antioxidants in maize grain. The idea is to alternately sow six rows of sterile standard quality hybrid and two rows of blue maize in commercial production. Five commercial ZP hybrids were crossed with a blue pop-corn population. Xenia effect caused by cross-pollination produced blue grain on all hybrids in the same year. Chemical analyses of the grains of five selfed original hybrids, five cross-pollinated hybrids and selfed blue popcorn pollinator were performed. Cross-fertilization with blue popcorn had different impact on antioxidant capacity and phytonutrients, increasing them significantly in some but not all cross-pollinated hybrids. Popcorn blue pollinator had higher values for all the analyzed traits than either selfed or cross-pollinated hybrids. Selfed vs. pollinated hybrids showed significant difference for total antioxidant capacity (p<0.1), total phenolics and total yellow pigments (p<0.01), with the increase of total phenolics and decrease of total yellow pigments in pollinated ones. Total flavonoids showed a little non-significant decrease in pollinated hybrids, while total anthocyanins were not detected in selfed yellow hybrids. Blue maize obtained this way has shown good potential for growing high quality phytonutrient genotypes.